Incidencia socioeconómica de los créditos y microcréditos para productores de ganado, otorgados por BanEcuador en la parroquia Canuto año 2018 - Palacios Verduga, José Darío (2021)
Canuto Parish promotes the intervention of the cattle ranchers' association through the contribution of credits from financial entities; in this way, the research was established that aims to evaluate the credits and microcredits granted by BanEcuador to Canuto cattle producers in 2018, the methodology was delimited as the deductive method that allowed to describe the essential characteristics of the study, inductive that had a direct connection to the studio; thus, for the development of the study, one was carried out identifying the credits granted by BanEcuador to the cattle producers of the Parish and their current situation; then the socioeconomic incidence was evaluated through the application of management indicators to the credits granted for the livestock development of the Parish, in this way an interview was applied to the president of the cattlemen's association specifying the types of financing that they make to the entities financial results and the results obtained, on the other hand, the applied survey managed to obtain relevant results, which allowed us to know the weaknesses and strengths of those involved. Finally, it was established through research that there is little time to cover the amount of credit and little capital to fulfill their activities; for this reason, the impact of the credits granted by BanEcuador to livestock producers was determined based on the socioeconomic study, considering that there are some shortcomings through the provision of information through financial entities to these livestock associations.